Pelayanan Angkutan Umum Perkotaan dan Kaitannya Dengan Subjective Well-Being Pengguna Angkutan Umum (Studi Kasus: Kota Surakarta) - Basrum, Revasari Puspita; Pradono, Pradono; Saraswati, Zenia F (Jurnal Perencanaan dan Pengembangan Kebijakan, 2024)
Transportation as a major component in the living system, is known to be one of the sub-indicators of a liveable city which is based on the main indicator of the availability of public and social facilities. This study examines the quality of urban public transportation services and its relationship with the subjective well being of public transportation users in Surakarta City. The public transportation mode in this study is the Batik Solo Trans Bus. This research approach uses Mix Method with quantitative and qualitative methods. And analyzed using coding analysis and Structural Equation Model (SEM). Based on 8 variabels, namely transportation attractiveness, information materials, route efficiency, service adequacy, user satisfaction, aesthetics, user service, and security quality. The results of this study indicate that the quality indicators of public transport services have implications for the welfare index of public transport users in Surakarta City. The results of this study can be taken into consideration and recommendations in improving the quality of public transport services in Surakarta City to improve the subjective well-being of public transport users of Batik Solo Trans Bus.